Modelo de predisposición adquirida para el consumo de marihuana: Estudio basado en una muestra de estudiantes universitarios argentinos - Rivarola Montejano, Gabriela; Michelini, Yanina; Pilatti, Angelina (Revista de Psicopatología y Psicología Clínica, 2022)
Acquired preparedness model for marijuana use: A study based on a sample of Argentinian college students Abstract: The present study analyzed, in a sample of Argentinian college students, the mediational role of marijuana expectancies in the relationship between impulsivity, frequency of marijuana use and related negative consequences. A sample of 353 college students (M age= 22.32; SD = 2.81) who had been using marijuana during the last year participated in the study. We assessed trait-like impulsivity (UPPS-P scale), marijuana expectancies (positive and negative), frequency of marijuana use during the last year and experienced negative consequences. Results support the acquired preparedness model. Positive marijuana expectancies mediated the effect of sensation seeking on frequency of marijuana use and negative consequences. Additionally, a higher level of positive urgency was associated with a higher number of negative marijuana expectancies that in turn was associated with a lower frequency of use and, like that, a lower number of negative consequences. The results may be useful for the development of preventive strategies targeting college students with increased levels of impulsivity and marijuana expectancies. Keywords: Acquired preparedness model; marijuana; expectancies; impulsivity; college students. Resumen: Este trabajo examinó, en estudiantes universitarios argentinos, el rol mediador de las expectativas hacia la marihuana (EM) en la relación entre impulsividad, frecuencia de consumo de marihuana y consecuencias negativas asociadas. Participaron 353 universitarios (M de edad = 22.32; DT = 2.81) con consumo de marihuana en el último año. Se evaluó impulsividad rasgo (escala UPPS-P), EM (positivas y negativas), frecuencia de consumo de marihuana durante el último año y consecuencias negativas experimentadas. Los resultados apoyan el modelo de predisposición adquirida. Las EM positivas mediaron el efecto de búsqueda de sensaciones sobre la frecuencia de consumo de marihuana y las consecuencias negativas. Además, un mayor nivel de urgencia positiva se asoció a mayor cantidad de EM negativas que, a su vez, se asoció a menor frecuencia de consumo y, por esa vía, a menor cantidad de consecuencias negativas. Los resultados pueden ser útiles para estrategias preventivas destinadas a universitarios con elevados niveles de impulsividad y EM. Palabras clave: modelo de predisposición adquirida; marihuana; expectativas; impulsividad; estudiantes universitarios.